2008
DOI: 10.1016/j.eurpsy.2007.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing patterns of antidepressants in Europe: Results from the Factors Influencing Depression Endpoints Research (FINDER) study

Abstract: Antidepressant prescribing patterns and factors influencing the choice of antidepressant for the treatment of depression were examined in the Factors Influencing Depression Endpoints Research (FINDER) study, a prospective, observational study in 12 European countries of 3468 adults about to start antidepressant medication for their first episode of depression or a new episode of recurrent depression. Selective serotonin reuptake inhibitors (SSRIs) were the most commonly prescribed antidepressant (63.3% patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
137
5
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(174 citation statements)
references
References 33 publications
22
137
5
7
Order By: Relevance
“…8 The finding of this study also similar with finding of other study from the West and multi-country study from East Asia. 5,11,12 However, the percentage of prescription of SSRIs in the present study is higher than that reported in these studies. In the present study Mirtazepine formed the 8% of the total antidepressant prescriptions.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…8 The finding of this study also similar with finding of other study from the West and multi-country study from East Asia. 5,11,12 However, the percentage of prescription of SSRIs in the present study is higher than that reported in these studies. In the present study Mirtazepine formed the 8% of the total antidepressant prescriptions.…”
Section: Discussioncontrasting
confidence: 56%
“…[5][6][7] In Indian studies also evaluated antidepressant prescription from multicentre study and single center. [8][9][10] To the best of our knowledge, this is the first study from central India to evaluate the antidepressant prescription pattern at Mental hospital and medical college centers.…”
Section: Discussionmentioning
confidence: 99%
“…Recent drug utilization studies; however, have demonstrated that SSRIs are the preferable antidepressants in many countries, as apparent from several studies across various populations. 8,12,13,14,15,16 Even so, SSRIs hold no superiority in terms of efficacy when compared to other antidepressants. 12 There is little published research concerning the prescribing pattern of antidepressants in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…Following this step, another revolutionary step was achieved in the 1980s, with the introduction of fluoxetine, the first member of the totally new antidepressants' family; i.e., the selective serotonin reuptake inhibitors (SSRIs). 11 Starting from the early 2000s, an increment in not only the numbers, but also the types of antidepressants was at hand for clinical practice, 12 which provides several choices for clinicians for a better and safer selection of medications for the management of depressive disorders. TCAs and tetracyclic antidepressants (TeCAs) were the first-line drugs for depression treatment over several years.…”
Section: Introductionmentioning
confidence: 99%
“…Selective serotonin reuptake inhibitors (SSRIs) are the most widely prescribed antidepressant drugs (Bauer et al, 2008). For the majority of relevant diagnoses, regular intake is recommended for months or even longer (Gaebel and Falkai, 2001).…”
Section: Introductionmentioning
confidence: 99%